Namibia Health Sector Public Expenditure Review - World Bank (World Bank, Washington, DC, 2019)
This Public Expenditure Review (PER) is the first for Namibia’s health sector. Namibia is an upper-middle income country that has made major progress in improving the standard of living for its population and reducing poverty. Still, with one of the highest Gini coefficients in the world, the society is highly unequal. In addition, the size of Namibia, combined with a low population density, makes it challenging for the health sector to provide universal access to quality health services across the country. The recent economic downturn has put fiscal pressure on the government and heightened the need for spending efficiency. Although government spending on health has been consistently close to the Abuja target of 15 percent, health outcomes are poor. The country faces a double burden of both communicable and non-communicable disease (NCDs), with high HIV/AIDS, stunting and maternal mortality rates that predominately affect the poor, and an increasing prevalence in non-communicable diseases that will contribute to costly treatments and growing health expenditures in the future. The Namibian government is committed to improve health outcomes. Namibia’s 5th National Development Plan (NDP5) for 2017-2022 aims to provide access to quality health care for its population, to increase Health Adjusted Life Expectancy (HALE) from currently 59 to 67.5 years, and to reduce mortality for mothers and children. To achieve this goal, the Ministry of Health and Social Services (MoHSS) has identified three strategic pillars for the health sector: (i) people’s wellbeing; (ii) operational excellence; and (iii) talent management. This health PER identifies several areas for the Namibian government to address in view of its goals.